Yield and quality of six summer annual forages - Nuwanyakpa, M.; Posler, Gerry L.; Bolsen, K.K.; Ilg, H. (Kansas State University. Agricultural Experiment Station, 2011)
In 1977, all summer annual forages studied produced excellent yields. Based on leafiness and regrowth ability, sudangrasses and pearl millet appeared to be best for early vegetative and boot cutting management. The sorghum-sudan hybrids had suitable yields and quality at all harvest stages. The hybrid forage sorghum appeared best suited for soft-dough-stage harvest although yields of pearl millet and sorghum-Sudan hybrids were also excellent.
Keywords: Beef; Yield quality; Quality; Forages